EFEKTIFITAS PENKES ONLINE TERHADAP PENINGKATAN PENGETAHUAN ORANG AWAM TENTANG BHD SAAT PANDEMIC - Zulmah Astuti; Misbah Nur Jannah (Husada Mahakam, 2021)
Introduction deaths caused by cardiac arrest out of the hospital, especially during the COVID-19 pandemic, tend to increase. This is partly due to the decrease in the implementation of basic life support by bystander due to fear of being infected with the covid 19 virus. Health education is needed to overcome this through online meetings. The purpose of this study was to determine the effectiveness of online health education in increasing the knowledge of lay person about basic life support during the pandemic. The research method is a quasi-experimental research conducted by Health Education on 34 people and measuring knowledge before and after Health Education. The data were analyzed using SPPS IBM 25. The results showed that there was a difference in knowledge before and after Health Education with a significance value of alpha (sig < 0.005) and based on the value of Ngain, it was found that health education was quite effective (56-75%) in increasing the knowledge of lay person. about basic life support during a pandemic. Conclusion Health education via online has proven to be quite effective in increasing the knowledge of lay person abaut basic life support during the pandemic Keywords: BLS, Cardiac arrest, Pandemic